The composition, origin and fate of complex mixtures in the maltene fractions of hydrothermal petroleum assessed by comprehensive two-dimensional gas chromatography - Ventura, G T; Simoneit, B R T; Nelson, R K; Reddy, C M (Organic Geochemistry, 2012)
Sedimentary organic matter in hydrothermal systems can be altered by high temperature fluids to generate petroleum. The saturated and aromatic fractions of these hydrothermal oils are compositionally similar to conventional oil with the exception that they often contain higher concentrations of polycyclic aromatic hydrocarbons (PAH) as well as substantial mixtures of coeluting organic compounds that produce dramatically rising signal on the baseline of gas chromatograms termed unresolved complex mixtures (UCMs). Little is known about the compounds that compose UCMs and why or how they form. This is in part due to an inability to discriminate between in situ and migrated components that characterize the petroleum generated in hydrothermal systems. However, UCMs are also a product of the limitations imbedded in analytical separation techniques. With the advent of comprehensive two-dimensional gas chromatography (GC × GC), a revision of what should constitute molecular complexity needs to be considered. We address these problems by comparing the molecular compositions of the maltene fractions of three previously published hydrothermal petroleum samples using time of flight-mass spectrometry (GC × GC–ToF-MS) and 12 hydrothermal petroleum samples in cores from three locales using comprehensive two-dimensional gas chromatography with flame ionization detection (GC × GC–FID). The sediment cores were collected from Middle Valley, located off the axis of the Juan de Fuca Ridge, and the Escanaba Trough, along the Gorda Ridge, both in the NE Pacific Ocean, as well as from the Guaymas Basin in the Gulf of California. We define a UCM in GC × GC data to be a condition in which ⩾25{%} of the detected peaks within a chromatographic area coelute in either the first or second dimension. In turn, complex (CM) and simple mixtures (SM) are defined as having 5–24{%} and and migrated components that characterize the petroleum generated in hydrothermal systems. However, UCMs are also a product of the limitations imbedded in analytical separation techniques. With the advent of comprehensive two-dimensional gas chromatography (GC × GC), a revision of what should constitute molecular complexity needs to be considered. We address these problems by comparing the molecular compositions of the maltene fractions of three previously published hydrothermal petroleum samples using time of flight-mass spectrometry (GC × GC–ToF-MS) and 12 hydrothermal petroleum samples in cores from three locales using comprehensive two-dimensional gas chromatography with flame ionization detection (GC × GC–FID). The sediment cores were collected from Middle Valley, located off the axis of the Juan de Fuca Ridge, and the Escanaba Trough, along the Gorda Ridge, both in the NE Pacific Ocean, as well as from the Guaymas Basin in the Gulf of California. We define a UCM in GC × GC data to be a condition in which ⩾25{%} of the detected peaks within a chromatographic area coelute in either the first or second dimension. In turn, complex (CM) and simple mixtures (SM) are defined as having 5–24{%} and
Keywords: HOV Alvin (Human Occupied Vehicle)